Mesin Panas Kuantum Partikel Relativistik pada Sumur Potensial 2 Dimensi: Heru Sukamto, Agus Purwanto, Bintoro Anang Subagyo - Heru Sukamto, Heru Sukamto; Agus Purwanto, Agus Purwanto; Bintoro Anang Subagyo, Bintoro Anang Subagyo (Jurnal Fisika dan Aplikasinya, 2025)
In this paper, we discuss quantum heat engine with relativistic particle medium in two-dimensional potential well. We chose Carnot-like engine model with isoenergetic and isoentropic expansion to both dimensions of potensial well. We took different expansion parameter to both dimensions. From the analytic calculation, we obtained heat engine eficiency with non-relativistic approach depend on the sizes of potensial well. However, if we took same expansion parameter both dimensions, then the value of heat engine eficiency was equal to 1 dimension case.